A COMPARATIVE ANALYSIS OF TAOISM AND COMPLEMENTARY REFLECTION (IBUANYIDANDA PHILOSOPHY) - Peter Bisong Bisong (Universitas PGRI Madiun, 2021)
This work examined the thoughts of Taoism as propounded by Lao-Tzu and Complementary Reflection as propounded by Asouzu to discover their nexus and their point of diversion. One basic difference between the two is that complementary reflection is not a religion but Taoism is at once a philosophy and a religion. Notwithstanding the differences in nuances, contents and emphasis, we discovered a striking similarity between the two thoughts – there are geared towards complementarity. However, I believe the major weakness of Taoism over complementary reflection surrounds the concept of Tao, which is a mysterious unverifiable principle of integration.